Development Strategies for Al-Qur'an and Hadith Learning Management at MIS Bidayatul Hidayah 2 Percut Sei Tuan - Efendi Sipahutar, Romat; Kalsum, Umi (Education Achievement: Journal of Science and Research, 2022)
This study examines the development strategies for Al-Qur'an and Hadith learning management at MIS Bidayatul Hidayah 2 Percut Sei Tuan, focusing on the effectiveness, challenges, and areas for improvement in delivering Islamic religious education. Using a qualitative descriptive approach, data were collected through interviews, classroom observations, and document analysis involving teachers, administrators, and students. The findings reveal that the structured lesson plans, interactive activities, and weekly assessments used by the school effectively engage students in understanding and memorizing Quranic verses and Hadith. However, challenges such as limited teaching resources, inadequate teacher training, and inconsistent parental involvement were identified as barriers to the program’s full potential. The study also highlights the potential for technology integration to enhance learning experiences and the importance of consistent evaluation to track both academic and behavioral progress. Addressing these challenges through improved resource allocation, enhanced training opportunities, stronger community partnerships, and technology use can further strengthen Al-Qur'an and Hadith learning at MIS Bidayatul Hidayah 2, fostering a deeper understanding of Islamic teachings among students.